Service Learning in Teachers and Students Mentoring for 2020 Bebras Challenge in Pandemic Era at Maranatha Bebras Bureau Christian University - Mewati Ayub; Maresha Caroline Wijanto; Adelia Adelia; Billy Susanto Panca; Doro Edi; Julianti Kasih; Hapnes Toba; Risal Risal; Meliana Christianti; Robby Tan; Daniel Jahja Surjawan (Journal of Innovation and Community Engagement, 2021)
Bebras Challenge is a competition for elementary to high school students to educate informatics and computational thinking, followed by sixty countries all over the world. Bebras Indonesia Community in coordination with the International Bebras Committee holds the challenge yearly. Indonesia has participated in the Bebras Challenge since 2016. Faculty of Information Technology Maranatha Christian University as a Bebras Bureau has also been involved in the challenge since 2016. To prepare students for Bebras Challenge, Maranatha Bebras Bureau holds a teacher workshop yearly. The Teacher Workshop supports teachers to strengthen students in practicing Bebras tasks. Data on students who participated in the Bebras Challenge at Maranatha Bebras Bureau indicates increasing numbers from 2016 until 2020. This paper describes a service learning for mentoring teachers and students in the Bebras Challenge, which was held in the pandemic year 2020. Teacher mentoring was using a service learning approach, where the lecturers provided training to the teachers and then the teachers would share their knowledge back to their students. There were advantages and disadvantages of the execution during the pandemic. Although in a distance learning condition, teachers and students were still enthusiastic to participate in Bebras Challenge. The number of students who followed the 2020 Bebras Challenge nearly five times compared to 2019 in the Maranatha Bebras Bureau. The scores of elementary school students who followed the challenge showed very good results. On the other side, the results of junior and senior high school students were not as good as the scores of elementary school students.